2022
DOI: 10.1186/s12903-022-02630-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early wound healing, pain intensity, quality of life and related influencing factors during periodontal surgery: a cross-sectional study

Abstract: Background This cross-sectional study assessed early wound healing, pain intensity, quality of life, surgical satisfaction, and related factors during periodontal surgery. Methods A total of 369 patients completed the questionnaire before undergoing periodontal surgery (baseline), immediately after the operation (phase I), on the day of suture removal (phase II), and one month later (phase III). The Early Wound Healing Score (EHS) was assessed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Almost all patients had mild-to-moderate postsurgical morbidity after ECL. This result is in good agreement with many studies that have shown that the overall incidence of postsurgical pain is low following periodontal surgery, and the intensity is mild for the majority of patients [15,[19][20]. Patients who undergo FL surgery have reported lower levels of bleeding on the day after the surgery and reduced levels of pain, swelling, and discomfort in the rst week.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Almost all patients had mild-to-moderate postsurgical morbidity after ECL. This result is in good agreement with many studies that have shown that the overall incidence of postsurgical pain is low following periodontal surgery, and the intensity is mild for the majority of patients [15,[19][20]. Patients who undergo FL surgery have reported lower levels of bleeding on the day after the surgery and reduced levels of pain, swelling, and discomfort in the rst week.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have shown a strong link between patient satisfaction and adherence to treatment, which is now recognized as a crucial factor in healthcare outcomes, including those in the eld of dentistry [14]. Therefore, patient satisfaction has been proposed as a key metric for assessing the overall effectiveness of periodontal treatment, allowing dentists to compare different approaches and identify areas for improvement [15].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the periodontal surgeon is to provide direct access to the affected area (periodontal pocket) and resect the gingiva and cratered bone to reduce pocket depth and create uniform bone contours. [29][30][31] Thus, the choice of treatment tactics depends on the stage of the disease. Present time for the treatment and prevention of periodontitis plasma therapy technique that can be used in combination with various therapeutic methods and drugs, including antibacterial anti-inflammatory, immunomodulatory.…”
Section: Introductionmentioning
confidence: 99%